Pengembangan Media Pembelajaran Interaktif Menggunakan Ispring pada Materi Perangkat Keras di SMP Kelas VII - Iman Gustiawan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to develop and validate the feasibility of interactive learning media based on iSpring on hardware material for junior high school students in grade VII. The conventional learning process is often less interesting and not optimal in conveying hardware concepts that tend to be abstract. Therefore, the development of this interactive media is expected to be an alternative in learning media in class and outside the classroom. This study uses the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The research stages include defining student needs and curriculum, media design, developing iSpring learning media products, and distributing and evaluating feasibility. The validation results from media experts showed a feasibility percentage of 92.22% and from material experts 100%. With an average validation value from material experts and media experts reaching 94.61%, this iSpring-based interactive learning media was declared very feasible for use in the learning process.